Some problems of the development of indirect stimulation of innovation activities of organizations performing R & D in the digital economy - A. O. Ryzhkov (Путеводитель предпринимателя)
A retrospective analysis of the definition of the term «innovative infrastructure» was carried out. Two conceptual approaches to defining the definition of «innovation infrastructure» - activity and component ones, focusing on various inalienable characteristics of the term under consideration are formalized. The thesis is substantiated that in the context of the digital economy the term «innovation infrastructure» requires rethinking and clarification. In the context of the deep integration of digital and cloud technologies in the structure and functions of the information subsystem of the innovation infrastructure, significant changes occur that require analysis and formalization. An introduction to the scientific background of the term «information and communication system» as a component of the innovation infrastructure, which most accurately identifies its informational aspect, taking into account the requirements of modern socio-economic realities, is proposed. There are three main characteristics that distinguish the information and communication system from the traditional information subsystem of the innovation infrastructure: the focus and stability of the interaction of the subjects within the information and communication systems; increasing the value of the ordered information flows and information services as separate elements of the information and communication system; increasing the value of the cognitive structure of social innovation knowledge within regional information and communication systems. As a key component of the information and communication system are considered information flows arising from the interaction of subjects of innovation. It is proposed to typologize all information flows on the basis of directing impact on five main types: production, knowledge, service, organizational and managerial, integration and diffuse. For visualization of the directing influences of information flows, the article presents the author’s model of the structural organization of information flows within the information and communication system. This model is accompanied by information on its basic elements and principles of operation. The main tasks on the problems of innovative development of information and communication systems are given: strengthening state support for the innovation infrastructure in terms of increasing the financing of R & D of industrial enterprises; centralization of management of regional information and communication systems based on the creation of special information centers; increasing the level of development of access technologies for data processing and storage.